Analyzing the Role of Automatic Voltage Regulator towards Excited Synchronous Generators on the Sultan Hasanuddin Training Ship - Hasiah, Hasiah; Mahadir, Mahadir; Risal, Syah (INTEK: Jurnal Penelitian, 2022)
Voltage instability in a synchronous generator can lead to system instability, affecting the quality and ability to transfer power to consumers. The worst-case scenario is load- shedding. To prevent this, the Automatic Voltage Regulator (AVR) is used to control the voltage stability of the synchronous generator. However, the AVR is often damaged, which prompted us to investigate its role in stabilizing the output voltage of the synchronous generator. This study was conducted on the Sultan Hasanuddin Training Ship owned by the Marine Science Polytechnic (PIP) Makassar using experimental research methods. Data collection techniques included observation, measurement, and documentation, and quantitative descriptive methods were used for analysis. Results indicated that the role of the AVR on the Sultan Hasanuddin Training Ship was insignificant since changes in generator load did not result in high fluctuations. The excitation current on the voltage amplifier or the output voltage of the synchronous generator remained within the working limit. This was proven by the generator's rotation speed, which ranged from 1470 to 1500 rpm, and a generator load of 36 to 38 kW.